Production scheduling in the TMC in Marel Iceland - Hrafnhildur Ýr Matthíasdóttir 1991- (2016)
To be capable of thriving in today’s competitive markets, the pressure on manufacturing companies to deliver products to their customer at the right time, at the right cost and of the right quality is constantly increasing. The main subject of this project is a real-world scheduling problem that originates in a production cell in Marel Iceland. The objective is to analyze the problem from a scheduling theory standpoint and answer the question, if by using the current resources in place, it is possible to improve the production scheduling process in order to minimize late deliveries to the customer. The current situation is explored and delivery reliability is introduced as a KPI. The problem is mathematically described as a formal notation in order to connect it to scheduling theory. The results indicate that with improved production scheduling, based on the capacity of each machine in the production cell, the delivery reliability can be increased. The results also indicate that the quality of data registration gives multiple disadvantages when trying to apply scheduling methods. However, with relatively manageable changes, and by using the right tools, the delivery reliability can indeed be increased from 88% to 100%. Furthermore, the time that goes into the current scheduling process can be reduced.